(untitled) (Journal of Asian Development Studies, 2025)
This study explores the phenomenon of English-Pashto code-mixing among university students in Swabi, a semi-urban district in Khyber Pakhtunkhwa, Pakistan. Drawing on sociolinguistic theories of bilingualism, identity, and language contact, the research investigates the frequency, patterns, and sociocultural motivations behind the integration of English lexical items into spoken Pashto. Using a qualitative-dominant mixed-methods approach, data were collected through naturalistic audio recordings of informal student conversations, semi-structured interviews, and a language attitudes questionnaire. Findings reveal that English insertions—primarily academic and technological nouns—are systematically embedded within Pashto syntax, serving both communicative and symbolic functions. Code-mixing was found to be most prevalent in educational, technological, and institutional contexts, with usage patterns influenced by gender, academic discipline, and socio-economic background. While students generally perceived English usage as a marker of modernity, education, and social prestige, some expressed concern over the erosion of linguistic purity and cultural identity. The study concludes that Pashto-English code mixing represents a localised and strategic adaptation to global linguistic pressures, reflecting the emergence of hybrid linguistic identities among Pakistani university students. Recommendations are provided for educators, policymakers, and researchers to accommodate better and understand bilingual realities in regional educational settings.